Review of Breast Abscess Cases at a Tertiary Hospital in Addis Ababa, Ethiopia - Suga Y; Kuehn T; W/Ammanuel G; Knfe G; Teklewold B (Dove Medical Press, 2023)
Yisihak Suga,1 Thorsten Kuehn,2 Gessesse W/Ammanuel,1 Goytom Knfe,1 Berhanetsehay Teklewold1 1Department of Surgery, St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Gynecological Oncology and Gynecologic Surgery, Klinikum Esslingen, Esslingen, GermanyCorrespondence: Yisihak Suga, Tel +251913470780, Email yisihaksuga12@gmail.com; yisihak.suga@sphmmc.edu.etBackground: Breast abscess is a prevalent cause of morbidity in women occurring in 0.4% to 11% of patients after mastitis. The majority are benign, but worrisome etiologies such as inflammatory cancer and concomitant immune-compromising diseases should be addressed when a non-lactating patient presents with a breast abscess. The problem is high among women in developing countries (1). The purpose of this study is to assess the magnitude, clinical presentation, and treatment of breast abscess patients at a tertiary hospital.Methodology: A descriptive cross-sectional study was conducted on all patients treated for breast abscesses from September 2015 to August 2020. A retrospective review of the clinical records was performed to collect data on sociodemographic, clinical, and management data using a data extraction form. The collected data were then cleaned and entered into SPSS for analysis.Results: Two hundred and nine patients were included in this study over 5 years and lactational breast abscess (LBA) is more prevalent,182 (87.1%) than non-lactational breast abscess (NLBA), 27 (12.9%). Bilateral breast abscesses occurred in 16 (7.7%) patients. Patients presented at a median duration of 11 days and had been breastfeeding for 2 or more months. A spontaneously ruptured abscess was detected in, 30 (14.4%) of the patients. Comorbidities identified include diabetes mellitus (DM) in, 24 (11.5%), Hypertension in, 7 (3.3%), HIV in, 5 (2.4%) of patients. All women were treated with Incision and Drainage and had a median volume of 60 mL of pus drained. Following surgery, all patients were given ceftriaxone in the immediate post-operative days and either cloxacillin,167 (80.3%), or Augmentin,41 (19.7%) antibiotics p on discharge. Follow-up data were available for 201 (96.1%) patients and the recurrence rate was 5.8%.Conclusions and Recommendations: Lactational breast abscesses are more common than non-lactational breast abscesses, particularly in primiparas. DM is the most common comorbidity in non-lactational breast abscesses and health-seeking behavior should be improved given the delayed presentation.Keywords: breast abscess, lactational, non-lactational, magnitude, clinical presentation